Enzymatic and chemical synthesis of new anticoagulant peptides. (27th July 2018) - Origone, Anabella; Bersi, Grisel; Illanes, Andrés; Sturniolo, Héctor; Liggieri, Constanza; Guzmán, Fanny; Barberis, Sonia
Abstract : In this study we report the enzymatic synthesis of N ‐α‐[Carbobenzyloxy]‐Tyr‐Gln‐Gln (Z‐YQQ), a new anticoagulant tripeptide. It was obtained using phytoproteases from the stems and petioles of Asclepias curassavica L. as catalyst in an aqueous–organic biphasic system formed by 50% (v/v) ethyl acetate and 0.1 M Tris–HCl buffer pH 8. The resulting peptide was compared with the analogous peptide Tyr‐Gln‐Gln (YQQ) produced by solid‐phase chemical synthesis. The in vitro anticoagulant activity of the aforementioned peptides was determined using Wiener Lab Test (Wiener, Argentina). The toxicological activity of the peptides was also determined. The enzymatically synthesized Z‐YQQ peptide acted on the extrinsic pathway of the coagulation cascade, delaying the conversion time of prothrombin to thrombin and fibrinogen to fibrin by 136 and 50%, respectively, with respect to the controls. The chemically synthesized YQQ peptide acted specifically on the intrinsic pathway of the coagulation cascade, affecting factors VIII, IX, XI, and XII from such cascade, and increasing the coagulation time by 105% with respect to the control. The results suggest that two new anticoagulant peptides (Z‐YQQ and YQQ) can be useful for safe pharmaceutical applications. Nevertheless, some aspects related to peptide production should be optimized. © 2018 American Institute of Chemical Engineers Biotechnol. Prog., 2018 © 2018 American Institute of Chemical Engineers Biotechnol. Prog., 34:1093–1101, 2018